Facial age cues and emotional expression interact asymmetrically: age cues moderate emotion categorisation - Craig, B.; Lipp, Ottmar (Routledge, 2017)
GroupFacial attributes such as race, sex, and age can interact with emotional expressions; however, only a couple of studies have investigated the nature of the interaction between facial age cues and emotional expressions and these have produced inconsistent results. Additionally, these studies have not addressed the mechanism/s driving the influence of facial age cues on emotional expression or vice versa. In the current study, participants categorised young and older adult faces expressing happiness and anger (Experiment 1) or sadness (Experiment 2) by their age and their emotional expression. Age cues moderated categorisation of happiness vs. anger and sadness in the absence of an influence of emotional expression on age categorisation times. This asymmetrical interaction suggests that facial age cues are obligatorily processed prior to emotional expressions. Finding a categorisation advantage for happiness expressed on young faces relative to both anger and sadness which are negative in valence but different in their congruence with old age stereotypes or structural overlap with age cues suggests that the observed influence of facial age cues on emotion perception is due to the congruence between relatively positive evaluations of young faces and happy expressions.